Rumpole and the primrose path - Mortimer, John Clifford (New York : Viking, 2003)
In a collection of stories, curmudgeonly London barrister Horace Rumpole, recovering from a heart attack, takes on a nasty head nurse at his run-down convalescent center as he investigates the mysterious death of an elderly patient.
Keywords: Legal stories, English; Detective and mystery fiction